The Effect of Learning with The Mindmapping Method Using Imindmap towards Student’s Analytical Ability - Dewi Dewantara (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This article aims to describe the difference of student’s analytical ability after applying learning with the mindmapping method using the iMindmap application. The type of this research is pre-experiment with one group pretest posttest design method. The number of research samples is 15 students of Physics Education Universitas Lambung Mangkurat. The data collection technique was using pretest and posttest. The aspects measured in seeing the students' analytical ability are matching, classifying, error analysis, generalizing, and specifying. Data were analyzed using paired t-test. The results of the t-test analysis obtained the value t = -6,510 with sig (2-tailed) = 0,000 which is smaller than the significance level of 0.05. The conclusion is that there is a difference between the initial analytical ability and the final analytical ability of students after applying learning with the mindmapping method using the iMindmap application. Keywords: mindmapping, iMindmap, analytical ability